The interplay between Pseudomonas aeruginosa and human macrophages and neutrophils - Muntaka, Sirina (2017)
Pseudomonas aeruginosa (PA) is an opportunistic pathogen that can cause infections in patients with compromised immunity including patients with neutropenia, HIV infection, burns, cancer, organ transplant surgery or in intensive care as well as Cystic Fibrosis (CF) patients. CF patients may have a T-helper (Th)-2 and Th-17-biased immune response which suggest that, either the absence of Th-1 and/or enhanced Th-17 responses may contribute to chronic PA infection with a deterioration of lung function in CF. A previous study in our laboratory showed that interferon (IFN)-γ production by peripheral blood mononuclear cells (PBMCs) from CF patients positively correlates with lung function, particularly in patients chronically infected with PA. In contrast, IL-17A levels correlated negatively with lung function especially in patients chronically infected with PA. These results agreed with the notion that IFN-γ and IL-17A play protective and detrimental roles, respectively, in CF disease. To explore the protective effect of IFN-γ in CF, the effect of IFN-γ alone or in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF), on the ability of human macrophages to control PA growth, resist the cytotoxicity induced by PA or promote inflammation was investigated previously in our laboratory. Treatment of macrophages with IFN-γ, in the presence and absence of GM-CSF did not alter bacterial growth or macrophage survival upon PA infection, but made the macrophages more pro-inflammatory. As neutrophils have been reported to be the key effector cells for the clearance of PA, there was therefore the need to include neutrophils in the macrophage cultures so as to determine how inflammatory conditions affect PA clearance. Although neutrophils are essential for protection against extracellular bacteria, neutrophil-dominated inflammation can compromise organ function by causing tissue damage. Optimal anti-bacterial immunity should harness the microbicidal activity of neutrophils while minimising their potential for causing injury. However, neutrophils do not act in isolation, they respond to cues provided by other cells such as macrophages, which influence their activation and life span. In vivo models have dominated the study of anti-bacterial immunity and there is a need of human models for the dissection of macrophage/neutrophil communication during bacterial infection. This work describes the development of a human macrophage/neutrophil infection assay and its use to model Th-1 (IFN-γ) - and Th-17 (IL-17A)-driven microbicidal activity and inflammatory potential upon infection. Results show that IFN-γ and IL-17A have opposite effects on the killing ability of macrophages and neutrophils co-cultures; bacterial killing was reduced by IFN-γ and promoted by IL-17A. In addition, macrophages and neutrophils specifically collaborated for the production of IL-1β and IL-1α and IFN-γ-treated co-cultures generated significantly less IL-1β and IL-1α compared to those treated with IL-17A. This effect was not observed with other cytokines such as TNF-α, IL-6, MIP-1α and MCP-1. Also, there was increased production of IL-1β upon addition of neutrophils to infected macrophage cultures and this depended on caspase-1 activity. Thus phagocyte co-cultures provide a suitable model of human anti-microbial immunity and unveil an unappreciated collaboration between macrophages and neutrophils in the promotion of IL-1-mediated inflammation. The reduction of inflammation in the presence of IFN-γ highlights the potential of IFN-γ as a therapeutic strategy in extracellular bacterial infections such as infections with PA.